Salinity fluctuation influences the toxicity of 1-octyl-3-methylimidazolium chloride ([C8mim]Cl) to a marine diatom Phaeodactylum tricornutum. (December 2022) - Liu, Qiaoqiao; Gao, Kun; Li, Linqing; Yang, Mengting; Gao, Zheng; Deng, Xiangyuan
Abstract: In this work, a marine diatom ( Phaeodactylum tricornutum ) was exposed to 1-octyl-3-methylimidazolium chloride ([C8 mim]Cl) for 96 h at three different salinities (25, 35, and 45 ‰) for investigating their interactive effects. Results showed that values of EC10 and EC50 at 96 h of exposure were 0.29, 1.06, 2.01 μg L −1 and 7.21, 7.71, 7.25 mg L −1 when the salinities were 25, 35, and 45 ‰, respectively, meaning that salinity fluctuation affected the toxicity of [C8 mim]Cl to this diatom. Changes in chlorophyll a contents and chlorophyll fluorescence parameters suggested that [C8 mim]Cl and salinity fluctuation had a significant interactive effect on the algal photosynthesis. In addition, soluble protein content and activities of antioxidant enzymes in algal cells changed significantly. Increased malondialdehyde contents indicated that the combined stresses could induce excessive production of reactive oxygen species leading to oxidative damage to the algal cells. Graphical abstract: Unlabelled Image Highlights: Interactive effects of [C8 mim]Cl and salinity fluctuation were firstly studied. [C8 mim]Cl and salinity fluctuation had interactive effects on the algal growth. The two factors caused a decrease in photosynthetic activity of this diatom. Contents of cellular components were remarkably affected by the two factors. Significant biochemical responses occurred in the diatom against the two factors.